Band-Limited Kernel Modifications for Regional Geoid Determination Based on Dedicated Satellite Gravity Field Missions - Featherstone, Will (Ziti Editions, 2003)
Previous modifications to Stokes's formula are based on either deterministic or stochastic considerations, with only one or the other being used exclusively in practice. This paper presents their band-limited combination, where stochastic modifications are used only in those parts of the gravity field spectrum where error variances are reliable, and deterministic modifications are used where they are not. This aims to optimise the filter-ing properties of the modified kernel such that the different components of the gravity field spectrum are weighted according to their known or perceived reliability. Because long-wavelength errors often occur in terrestrial gravity anomalies, the use of a low-degree spheroidal Stokes kernel is advocated so as to realise the full benefit of geoid models computed from the current and planned dedicated satellite gravity field missions.